Improving water governance in Central Asia through application of data management tools - Abdullaev, Iskandar; Rakhmatullaev, Shavkat A.; Platonov, Alexander; Sorokin, D. (Informa UK Limited, 2012)
Contemporary water management decisions use many sources and forms of data. The paper discusses the implementation results of data management activities in the water sector carried out in five countries of the Central Asia region. Geoinformation systems, remote sensing tools and databases have been applied worldwide for improving water resources management with differing levels of success. Water management organisations, equipped with data management tools will have better capacities to adapt their decision-making in the changing availability and scarcity of water resources. Application of data management tools for improving collection, storage and processing of data and information are a first step towards improved water governance.